Development of an in vitro human liver system for interrogating nonalcoholic steatohepatitis - Feaver, Ryan E.; Cole, Banumathi K.; Lawson, Mark J.; Hoang, Stephen A.; Marukian, Svetlana; Blackman, Brett R.; Figler, Robert A.; Sanyal, Arun J.; Wamhoff, Brian R.; Dash, Ajit (JCI insight, 2016)
A barrier to drug development for nonalcoholic steatohepatitis (NASH) is the absence of translational preclinical human-relevant systems. An in vitro liver model was engineered to incorporate hepatic sinusoidal flow, transport, and lipotoxic stress risk factors (glucose, insulin, free fatty acids) with cocultured primary human hepatocytes, hepatic stellate cells (HSCs), and macrophages. Transcriptomic, lipidomic, and functional endpoints were evaluated and compared with clinical data from NASH patient biopsies. The lipotoxic milieu promoted hepatocyte lipid accumulation (4-fold increase, < 0.01) and a lipidomics signature similar to NASH biopsies. Hepatocyte glucose output increased with decreased insulin sensitivity. These changes were accompanied by increased inflammatory analyte secretion (e.g., IL-6, IL-8, alanine aminotransferase). Fibrogenic activation markers increased with lipotoxic conditions, including secreted TGF-β (>5-fold increase, < 0.05), extracellular matrix gene expression, and HSC activation. Significant pathway correlation existed between this in vitro model and human biopsies. Consistent with clinical trial data, 0.5 μM obeticholic acid in this model promoted a healthy lipidomic signature, reduced inflammatory and fibrotic secreted factors, but also increased ApoB secretion, suggesting a potential adverse effect on lipoprotein metabolism. Lipotoxic stress activates similar biological signatures observed in NASH patients in this system, which may be relevant for interrogating novel therapeutic approaches to treat NASH.